Journal of Monetary Economics (New York Elsevier North Holland, Inc., 1995)
The Journal of Monetary Economics publishes important research contributions to a wide range of modern macroeconomic topics including work along empirical, methodological and theoretical lines. In recent years, these topics have been: asset pricing; banking, credit and financial markets; behavioral macroeconomics; business cycle analysis; consumption, labor supply, and saving; dynamic equilibria (theory and computational methods); economic growth and development; expectation formation, information and aggregate economic activity; fiscal shocks and fiscal policies; expectation formation; forecasting, macroeconometrics...
The JME publishes eight volumes each year. Two of the issues each year are dedicated to the Carnegie-Rochester-NYU Conference on Public Policy. Every two years, the JME publishes a ninth volume with the proceedings from a conference on macroeconomic policy sponsored by the Study Center Gerzensee of the Swiss National Bank. Last issue received vol.45 (2000) #1.
Keywords: Financial economics; MONEY; FINANCE; MACROECONOMICS; MONETARY POLICY; FINANCIAL MARKET; INTERNATIONAL FINANCE; PERIODICALS